El papel de la comunidad universitaria en el pos-acuerdo o pos-conflicto en Colombia (2016)
To Colombia, a historical stage opens up, the construction of peace after signing the agreements, which aim to close a long and bloody armed confrontation between the FARCEP guerrillas and the Government of Colombia